2019
DOI: 10.1177/0016986219828073
|View full text |Cite
|
Sign up to set email alerts
|

On Deciding to Accelerate: High-Ability Students Identify Key Considerations

Abstract: Acceleration is a well-researched educational intervention supporting positive outcomes for high-ability students. However, access to acceleration may be restricted due to educators’ misapprehensions about this practice. To better understand whether students share educators’ concerns, our study explored 26 high-ability students’ beliefs about important considerations in grade-based acceleration. Seventeen high-ability students who had accelerated (age 9-14 years) participated in group concept mapping activitie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 36 publications
1
5
0
Order By: Relevance
“…In this sense, general conclusions which may be extracted from this work and concerning data previously shown, it can be confirmed that two intervention modalities exist: first of all, the acceleration concerning an academic year further than the one in which the student has officially joined [ 35 , 36 , 37 , 38 ]; secondly, curricular enrichment programmes [ 38 , 39 , 40 , 41 , 42 ]. However, these latter are more disperse and not always fulfill students’ expectations.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…In this sense, general conclusions which may be extracted from this work and concerning data previously shown, it can be confirmed that two intervention modalities exist: first of all, the acceleration concerning an academic year further than the one in which the student has officially joined [ 35 , 36 , 37 , 38 ]; secondly, curricular enrichment programmes [ 38 , 39 , 40 , 41 , 42 ]. However, these latter are more disperse and not always fulfill students’ expectations.…”
Section: Discussionsupporting
confidence: 82%
“…Despite this positive assessment, the importance of the consolidation of an inclusive social climate, in which they are provided with opportunities and support for this adaptation, was indicated. Similarly, research performed by Dare, et al [ 36 ] also included the students’ opinion and own experience with 26 high-ability students participating in the study, of whom 19 had accelerated. The results showed strong agreement with this measure, as it provided a better learning environment for those progressing from one year to the next when challenging activities depending on their abilities were performed.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Noble and Childers’ (2008) survey study conducted in the same geographical region) or the same country (cf. Dare et al, 2019; Kanevsky, 2011; Kruszynski, 2014). It is also important to mention that the radical acceleration program referred by our participants represents only a form of this type of gifted programming.…”
Section: Discussionmentioning
confidence: 99%
“…Although considered essential in gifted education (Mayer, 2005;Rogers, 2007;, it is also surrounded by some controversy, especially when it comes to its grade-based forms (e.g., early entrance to school/ college, grade skipping), wherein the student is placed within an older age cohort. Nevertheless, in the field of academic giftedness, accelerationincluding radical grade-based acceleration of 2+ years-is a wellresearched intervention (Dare et al, 2019;Neihart, 2007), with findings of quantitative studies usually testifying to its beneficial effects, both shortterm and long-term, on students' academic achievement, motivation, and productivity (e.g., Rinn & Bishop, 2015;Sayler & Brookshire, 1993). Available findings also suggest that acceleration does not entail any significant socio-emotional risks, yet we must agree with Gronostaj et al (2016) that little is known about these effects, and that a large-scale quantitative approach cannot depict the complexity of the experience of grade skipping from an individual perspective.…”
Section: Playing Fast Forward: Accelerated Talent Developmentmentioning
confidence: 99%